PENGARUH KUALITAS E-LEARNING, SELF-EFFICACY, DAN INTERAKSI TERHADAP STUDENT SATISFACTION PADA PEMBELAJARAN ONLINE DI SEKOLAH MENENGAH KEJURUAN - Nabila Dini Syara; Endang Sri Andayani (Universitas Muria Kudus, 2022)
The purpose of this study was to determine the effect of e-learning quality, self-efficacy, and interaction on student satisfaction during online learning.The research method used is quantitative with explanatory research. The research was conducted on 261 students with expertise in Business and Management at SMK Negeri 2 Blitar. Data were collected using a questionnaire distributed online and then analyzed using multiple linear regression with the help of SPSS IBM version 21.The results of the study found that the services provided by the teacher were quite responsive, friendly, and fair when students experienced system problems so that it had an impact on student satisfaction in using e-learning. Then, it was also found that students had high confidence in operating the e-learning platforms used by teachers (Moodle and Google Classroom), although they lacked confidence in doing assignments and completing exams. Furthermore, during online learning, the average student has low interaction with the teacher. Some students tend to be passive when the teacher asks questions. It can be concluded that there is a positive and significant influence between the quality of e-learning, self-efficacy, and interaction on student satisfaction.